Uma estratégia para o ensino de função afim - Silva, Jhonison Alves da (Brasil, 2023)
This work presents a teaching strategy that uses mathematical modeling to teach the affine function in the context of fueling Flex cars. The objective of the strategy is to develop a teaching method that allows students to understand the affine function in the context of fueling Flex car in a meaningful way. For this, a case study was carried out involving 21 students of the 2nd year of high school at a State School in Itacoatiara/AM. The teaching proposal consisted of an experimental class lasting 200 minutes, in which students were encouraged to mathematically model, represent and analyze the cost of fueling Flex car. The results obtained indicated that the teaching strategy was effective in promoting the understanding of the idea of an affine function and some of its properties, in addition to arousing students' interest in this learning process.